Dampak Kualitas Sumber Daya Manusia Profesionalisme kerja Dan Komitmen Kerja Terhadap Kinerja Pegawai : Studi Kasus Kantor Balai Taman Nasional Siberut Padang - Helma Sutarni; Sophan Sophian (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to examine the quality of human resuorces. work professionalism and work commitment at the siberut padang national park office. This research uses a quantitative method with a population ot 40 respondents and a ssmple of 40 respondrnts. Uses multiple linear regression to application. The results of the research show that the quality of human resources has a positive and significant effect on employee performance at the siberut padang national park hall office, work professionalism has a positive and significant effect on empoloyee performance at the siberut padang national park haal office, work commitment has a positive and significant effect on employee performance at the siberut padang national park hajj office